Reversible breaking and forming of Metal-Ligand coordination bonds: Temperature-Triggered Single-Crystal to Single-Crystal transformation in a Metal-Organic framework - Bernini, Maria Celeste (2009)
[Yb(C4H4O4)15] undergoes a temperature-triggered single-crystal to single-crystal transformation. Thermal X-ray single-crystal studies showed a reversibly orchestrated rearrangement of the atoms generated by the breaking/formation of coordination bonds, in which the stoichiometry of the compound remains unchanged. The transformation occurs on heating the crystal at «130 °C. This uncommon behavior was also studied by thermal methods, FTIR spectroscopy, and thermodiffrac-tometry. Both polymorphs, a (room-temperature form) and b (high-temperature form), are proven to be active heterogeneous catalysts; the higher catalytic activity of b is owed to a decrease in the Yb coordination number. A mechanism based on spectroscopic evidence and involving formation of the active species Yb-O-OH is proposed for the sulfide oxidation.